F1 HYBRIDS BREEDING OF RADISH (RAPHANUS SATIVUS L.) ON THE BASIS OF MALE STERILE LINES - G. F. Monakhos; A. A. Mironov; S. M. Tiukhanova (Овощи России)
The line fixers of sterility from the other pairs with genotype TsitNrfrf are encouraged to use for off-patent biological copyright protection paternal pollinating lines. In this case, the F1 hybrids will always have a TsitSrfrf genotype and will be sterile, which makes it impossible to obtain F2 progeny.